2023
DOI: 10.1186/s12879-023-08387-6
|View full text |Cite
|
Sign up to set email alerts
|

Organism type of infection is associated with prognosis in sepsis: an analysis from the MIMIC-IV database

Abstract: Background Sepsis has a high mortality rate, which is expensive to treat, and is a major drain on healthcare resources; it seriously impacts the quality of human life. The clinical features of positive or non-positive blood cultures have been reported, but the clinical features of sepsis with different microbial infections and how they contribute to clinical outcomes have not been adequately described. Methods We extracted clinical data of septic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Factors reported to be associated with the risk of sepsis include both personal (e.g., demographic [6], genetic [7], health behaviors [8], and comorbid conditions [9]) and community-level (e.g., social vulnerability [10], access to health care [11], urbanicity [12], and environmental exposures [13]) domains. The factors associated with case fatality among septic patients generally include similar personal [3,8,14] and community-level [11,[15][16][17] domains as those associated with the risk of sepsis, as well as infection characteristics [18,19], severity of illness [18], processes of care [20], and hospital characteristics [21][22][23][24]. Variations in exposure to these factors across race and ethnicity groups may contribute to the documented race and ethnicity-related disparities in sepsis-related mortality [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Factors reported to be associated with the risk of sepsis include both personal (e.g., demographic [6], genetic [7], health behaviors [8], and comorbid conditions [9]) and community-level (e.g., social vulnerability [10], access to health care [11], urbanicity [12], and environmental exposures [13]) domains. The factors associated with case fatality among septic patients generally include similar personal [3,8,14] and community-level [11,[15][16][17] domains as those associated with the risk of sepsis, as well as infection characteristics [18,19], severity of illness [18], processes of care [20], and hospital characteristics [21][22][23][24]. Variations in exposure to these factors across race and ethnicity groups may contribute to the documented race and ethnicity-related disparities in sepsis-related mortality [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Both IL-6 and C reactive protein were significantly greater with Gram-negative bacteria in a study of 515 culture positive blood samples from bacteraemia patients [162]. Similar studies have also found vastly increased cytokine profiles in Gram-negative bacteria compared with Gram-positive bacteria, with both pro and anti-inflammatory cytokines vastly increased in Gram-negative sepsis infections [163], which can influence disease as Gram-negative bacteria were found to be a major risk factor for sepsis prognosis [164].…”
Section: Cells and Pathways Affected By Sepsis 1421 Lps Theory Of Sepsismentioning
confidence: 65%